Dampak Situasi Sebelum dan Sesudah Pandemi COVID-19 Terhadap Volatilitas Harga Saham LQ45 - Hutauruk, Martinus Robert (Jurnal Riset Akuntansi dan Keuangan, 2021)
The study aims to investigate the effect before and after the COVID-19 pandemic on the share price ofÂ LQ45 on the Indonesia Stock Exchange in 2019 and 2020. This study uses share price data from 45 companies listed in the LQ45 stock group on the Indonesia Stock Exchange. Data were analyzed using IBM SPSS Version 26 with a paired sample difference test model (compare means paired-samples t-test). This study found that before and after the COVID-19 pandemic had a positive and insignificant effect on the LQ45 share price on the Indonesia Stock Exchange. Companies with core mining businesses experienced the highest price increase after the pandemic or reached a 47.26 percent increase, while companies in the property sector did not experience an increase or decrease. Companies in the clothing and equipment retail sector experienced the highest decline reaching -67.93 percent after the pandemic.Keywords.TheÂ COVID-19 Pandemic;Stock Price;IDX-LQ45;Investment